2018
DOI: 10.21776/ub.jkb.2018.030.02.7
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara Status Kontrol Glikemik, Vitamin D dan Gizi pada Anak Diabetes Melitus Tipe 1

Abstract: <p>Di beberapa negara barat kasus DM tipe-1 adalah 5-10% dari kasus  diabetes, dan lebih dari 90% penderita diabetes pada anak dan remaja adalah DM tipe-1. Vitamin D berperan penting dalam membangun dan memelihara mineralisasi tulang. Defisiensi vitamin D dapat menyebabkan penekanan bone turnover sehingga menyebabkan gangguan kecepatan tinggi badan. Kontrol glikemik yang buruk berupa HbA1c yang tinggi dapat menyebabkan berat dan tinggi badan tidak naik secara adekuat. Penelitian ini bertujuan untuk membu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…In contrast, Rianti's study (2017) found that the majority of respondents who experienced Type 1 DM were female as many as 37 people (62%) (Rianti, 2017). Meanwhile, in 2018 there was also a study which found that most children with type 1 DM aged 1-18 years, who were treated at Dr. Saiful Anwar Hospital Malang, were mostly female, consisting of 16 people (57%) (Indriyani, 2018). In addition, in a recent study the majority of Type 1 Diabetes was also experienced by females aged >12-19 years as many as 21 people (67.7%) (Kusumastuty, et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, Rianti's study (2017) found that the majority of respondents who experienced Type 1 DM were female as many as 37 people (62%) (Rianti, 2017). Meanwhile, in 2018 there was also a study which found that most children with type 1 DM aged 1-18 years, who were treated at Dr. Saiful Anwar Hospital Malang, were mostly female, consisting of 16 people (57%) (Indriyani, 2018). In addition, in a recent study the majority of Type 1 Diabetes was also experienced by females aged >12-19 years as many as 21 people (67.7%) (Kusumastuty, et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…that found the mean HbA1c levels was 9.77 ± 1.42%. Another study by Indriyani and Adji [17] reported that 18 of 28 children with T1DM had HbA1c more than 9%. Wulandari [18] also reported that 73% of 26 children with T1DM had HbA1c levels more than 7.5%.…”
Section: Discussionmentioning
confidence: 98%
“…Beberapa jenis penyakit yang berkaitan dengan fungsi imun dikaitkan dengan status kadar serum vitamin D (25(OH)D) di dalam tubuh. Pada review ini terdapat tiga artikel yang melihat hubungan kadar serum 25(OH)D dengan penyakit Diabetes Melitus Tipe 1 yaitu penelitian yang dilakukan olehDwi dkk (2015),Wibisono dkk (2016) danIndriyani & Adji (2018). Tuberculosis dan tingkat keparahan penyakit juga diduga berkaitan dengan status kadar serum 25(OH)D seperti pada penelitian yang dilakukan olehSetiabudiawan (2010) danMasnadi & Ihsan (2017).Diabetes Melitus Tipe 1 merupakan penyakit autoimun kronis yang disebabkan oleh rusaknya sel β pankreas sebesar 70-90% dan menjadi penyebab kegagalan produksi insulin(Korn et al, 2009;McGeachy et al, 2008).…”
unclassified